2021
DOI: 10.1002/jmv.27180
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus spread in children during the COVID‐19 pandemic despite social restrictions—A nationwide register study in Finland

Abstract: Social restrictions during the coronavirus disease 2019 pandemic strongly affected the epidemiology of influenza and respiratory syncytial virus (RSV). As rhinovirus seemed to spread despite the restrictions, we aimed to analyze rhinovirus epidemiology in children during the pandemic. This register‐based study used data from the Finnish Infectious Disease Register. Nationwide rhinovirus findings from July 2015 to March 2021 were included and stratified by age (0–4, 5–9, and 10–14). Cumulative 14‐day incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…Meanwhile, the impact of NPIs on some other respiratory viruses was more limited in Guangzhou. Such phenomenon was also reported in Australia, Finland, Italy, Japan, the US and elsewhere (Sberna et al, 2020;Sullivan et al, 2020;Kuitunen et al, 2021;Takashita et al, 2021). In particular, RHV was also reported to circulate as usual among children in Finland (Kuitunen et al, 2021) or even higher than usual in Japan and Australia (Sullivan et al, 2020;Takashita et al, 2021), during the period with various control measures against COVID-19.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Meanwhile, the impact of NPIs on some other respiratory viruses was more limited in Guangzhou. Such phenomenon was also reported in Australia, Finland, Italy, Japan, the US and elsewhere (Sberna et al, 2020;Sullivan et al, 2020;Kuitunen et al, 2021;Takashita et al, 2021). In particular, RHV was also reported to circulate as usual among children in Finland (Kuitunen et al, 2021) or even higher than usual in Japan and Australia (Sullivan et al, 2020;Takashita et al, 2021), during the period with various control measures against COVID-19.…”
Section: Discussionmentioning
confidence: 61%
“…Such phenomenon was also reported in Australia, Finland, Italy, Japan, the US and elsewhere (Sberna et al, 2020;Sullivan et al, 2020;Kuitunen et al, 2021;Takashita et al, 2021). In particular, RHV was also reported to circulate as usual among children in Finland (Kuitunen et al, 2021) or even higher than usual in Japan and Australia (Sullivan et al, 2020;Takashita et al, 2021), during the period with various control measures against COVID-19. In Guangzhou, we observed weaker suppression of non-enveloped viruses (RHV, ADV in our study) compared to enveloped viruses (influenza, RSV and HMPV in our study), as have also been reported in South Korea (Park et al, 2021).…”
Section: Discussionmentioning
confidence: 61%
“… 7 , 37 Increased rhinovirus activity was reported previously in Australia 38 and North America 39 when children returned to school from vacation, and more recently in New South Wales, Western Australia, New Zealand, the United Kingdom and Europe following the easing of COVID‐19 restrictions. 5 , 7 , 12 , 35 , 40 , 41 In addition to being transmitted directly and indirectly by respiratory secretions, rhinoviruses can also be shed in stools. 42 Moreover, it is a non‐enveloped virus, which is less susceptible to alcohol‐gel based hand sanitisers recommended during the COVID‐19 pandemic and it survives on surfaces for prolonged periods.…”
Section: Discussionmentioning
confidence: 99%
“…In a study based in Finland, social restrictions were associated with a decline in influenza and respiratory syncytial virus [ 14 ]. However, non-pharmaceutical interventions, including face masks or improved hygiene measures, were not effective in preventing the spread of rhinovirus in children [ 16 ]. As viral upper respiratory tract infections have a casual role with eustachian tube obstruction and abnormal middle ear pressure, the global and regional prevalence of different viruses of varying virulence could play a role in the incidence of conditions in pediatric otolaryngology [ 17 ].…”
Section: Discussionmentioning
confidence: 99%